Next-Generation Leadership Development: A Management Succession Perspective. - Tang, Joseph Kie Kuong; Wan Sabri, Wan Hussin (2020)
Purpose – This research study focusses on the succession challenges in small-medium outboard marine businesses of Malaysian Chinese family ownership. The founder-owners face challenges in convincing the next-generation memberstoestablishtheircareerswithinthefamilybusinessandtoensuresuccessionsarein place to safe guard the family’swealth.Agapexistsintheresearchliteraturesconcerningsuchfamilybusiness owners; and their experiences would provide valuable information to other Malaysian Chinese family businesses planning to start the succession journey. Design/methodology/approach – An exploratory case study methodology to research five Malaysian Chinese family businesses cases in Klang Valley, Selangor, Malaysia, is used in this study. The primary qualitative data were obtained through in-depth, semi-structured interviews and observations. The research data lead to the identification of the following themes:generational change affects thesurvivalofsmall-medium Malaysian Chinese family-owned businesses; the founder-owners’ intention and desire for business to pass to the next generation give rise to the imperative of succession; the founder-owners’ motive and goals, family context and the business nature would determine a large part to how the succession plans are carried out and theupbringing,expectationandobligationswoulddeterminehowthenextgenerationsofchildrenwouldview the prospect of taking over the family business. From this, a succession model that detailed an inclusive approach to succession planning process between the two generations is established. Research limitations/implications – A small purposive sample is included, and it is recommended that a larger and more diverse sample be collected in future studies. This study follows a nuclear family structure of parents and children. If more Chinese family businesses are selected based on a wider set of family members such as uncles and cousins, the findings may differ. Social implications – This researchstudy could alsofacilitateother Malaysianfamily businesses to rethink and refocus on the importance of undertaking an inclusive approach to succession planning and also help potentialnext-generationsuccessorsinunderstandingandworkingtowardsattainingthequalitiesthatfamily firms look for in future leaders. Originality/value –Theresearchersummarizesthestudyfindingsintoamanagementsuccessionmodel.An inclusive succession approach is needed to overcome these challenges and would enable sustainability, continuity and longevity of the family business. This would help the family business to understand that successionisnotasingleeventbutaprocessthatneedstobeplannedtogetherwiththenext-generationfamily members over a certain period of time.